Online Disinformation and the Palestine-Israel Conflict: How Indonesian Netizens Navigate Truth and Bias (Palestine Issues on Indonesian Society, 2024)
This paper explores the role of online disinformation in shaping public opinion in Indonesia regarding the Palestine-Israel conflict. With the rise of social media, Indonesian netizens increasingly engage in debates over the conflict, often encountering competing narratives and biased information. The study investigates how digital platforms such as Twitter, Facebook, and WhatsApp are used to disseminate both fact and misinformation, influencing Indonesian perspectives on Palestine. It also explores the strategies employed by Indonesian social media users to navigate these complexities, including fact-checking, selective sharing, and the creation of counter-narratives. The paper assesses the role of online activism, particularly within Indonesian Muslim communities, in amplifying the Palestinian cause and countering pro-Israel rhetoric. It further examines the impact of digital disinformation on political discourse, mobilization, and Indonesian foreign policy. The study concludes by offering recommendations for improving media literacy and combating disinformation in the Indonesian digital space.